(untitled) (Baltic Journal of Sport and Health Sciences, 2019)
Background. Research aimed at the analysis of self-perceptions of students of foreign language anxiety in the classroom context in relation to its effect on foreign language acquisition. It focused on foreign language, as a skill needed for versatile education, which would lead to a successful career in sports or would aid in pursuing health enhancing leisure activities later in life. Methods. The qualitative approach of research was adopted in this study. Twenty subjects involved in the study programs as Sports Coaching at the Lithuanian Sports University and Medicine at the University of Health Sciences participated in the research. A semi-structured interview was conducted by the researchers based on 10 open-ended questions about foreign language anxiety. Results. Although the perceptions of students’ own English language competence were found to be an important source of anxiety for the interviewed students, most of the respondents perceive the necessity of trying to cope with stress and anxiety themselves. In addition, instructors appeared to be creating the feeling of relaxation rather than being the anxiety-provoking ones in the classroom. Conclusion. Awareness of the fact that FLA really exists and appears to be an obstacle for students’ academic achievement needs to be acknowledged. To address this issue, collaboration rather than competition must be implemented as a tool in classes for further advancement in learning. Therefore, these measures might help to reinforce self-esteem and achieve better results in the foreign language classroom and, thus, in the overall goal of studies in the student learning process.